CSR as a moderator and ESG as a mediator in the relationship between gender diversity and financial performance - Silvana Juliant Dwi Damayanthi; Ahmad Juanda; Agung Prasetyo Nugroho Wicaksono (Assets: Jurnal Akuntansi dan Pendidikan, 2025)
This study investigates the impact of board gender diversity on financial performance, considering ESG as a mediator and CSR as a moderator. Secondary data were obtained from financial reports, governance, ESG, and CSR scores of non-financial firms listed on the Indonesia Stock Exchange for 20172024. The analysis applied Hayes Model 5. Results indicate that board gender diversity does not directly affect financial performance but indirectly influences it through ESG disclosure. CSR has a positive direct effect on financial performance but does not moderate the relationship. These findings emphasize ESG as the main mechanism linking board diversity to financial outcomes and highlight CSRs direct contribution to profitability.